Introduction of Open Journal System in the Framework of Supporting Scientific Publications for Physical Education Teachers Kuburaya District, West Kalimantan - Putra Perdana, Rahmat; Touvan Juni Samodra, Y.; Gandasari, Maharani; Firsta Yosika, Ghana; Dwi Puspita Wati, Isti; Supriatna, Eka; Gustian, Uray; Rubiyatno; Sastaman, Putra (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
One way to improve teacher professionalism is by encouraging teachers to write. The next step, once the writing is completed, is to publish it. Publishing before 2019 was still mostly done manually using printed journal books. Starting from 2019 until now, journals have begun to switch to online publishing. With online publishing, teachers automatically have to understand the procedures that apply in the open journal system (OJS) when sending articles. To bridge this need, Community Service is carried out so that teachers understand OJS which is now starting to become grounded. At least material on how to adjust templates, do submets, go through the process of review, copy editing, publishing and fees as a writer. This series of activities was given to teachers with the result that all teachers 100% understood the processes that occurred in the OJS journal.